Factors of background, input and process associated with Mathematics performance: A Multilevel analyses - Moreira Mora, Tania Elena (2013)
Abstract. The aim of this research was to determine the association of context, entrance background, and process factors with the academic performance in the course of General Mathematics from the integral perspective of the CIPP model. The study was based on the application of the lineal regression model. The participating students (level one) were enrolled in the course General Math in year 2010 and the second sample (level two) was comprised by the professors teaching that same course. Findings provided evidence relating the students’ performance to their academic history (context), the student-instructor interaction and the methodological strategies (process), as well as instructor´s characteristics (entrance). Finally, the articulation of the CIPP model with the multilevel analysis allowed an integral approach to a multifactor educational phenomenon